Liver Enzyme Biomarkers Before or in Early Pregnancy as Predictors for Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis - Pratama, Samuel; Aulia, Rizka Dwi; Jazilah, Indi; Lauren, Brigitta Cindy (Journal of the ASEAN Federation of Endocrine Societies, 2026)
Background. Liver enzymes may reflect early metabolic disturbances and insulin resistance preceding gestational diabetes mellitus (GDM). This systematic review and meta-analysis evaluated whether liver enzyme biomarkers measured before or in early pregnancy are associated with subsequent development of GDM. Methodology. PubMed, Cochrane, EBSCOHost, and SCOPUS databases were searched through May 2025 for observational studies or trials assessing pre- or early pregnancy liver enzymes in relation to GDM development. Pooled mean differences (MD) and odds ratios (OR) with 95% confidence intervals (CI) were calculated using a random-effects model. Risk of bias was assessed using RoB 2.0 and ROBINS-E; certainty of evidence was evaluated using GRADE. Results. Twenty-seven studies were included in the analyses. GDM was associated with higher AST (MD 0.97 U/L; OR 1.42), ALT (MD 2.38 U/L; OR 1.69), GGT (MD 3.77 U/L; OR 2.57), and hepatic steatosis index (HSI) (MD 2.82; OR 2.19). ALP showed no significant mean difference but an elevated GDM risk (OR 1.47). Substantial heterogeneity was observed with very low certainty of evidence across outcomes. Conclusion. Elevated liver enzymes, especially GGT and HSI, are associated with increased GDM risk at a population level. However, high heterogeneity and very low certainty of evidence limit current clinical applicability, warranting further prospective validation.